The Least Developed Countries Report 2022 - United Nations Conference on Trade; Development (United Nations, 2022)
LDCs, which bear the least historical responsibility for climate change, are on the front lines of the climate crisis. The Report highlights the development strategies and policies which they need to enact to reach the ambitious objectives to which they have committed, and the painful trade-offs between climate action and accelerated progress towards fulfilling their right to development they will need to navigate in the challenging international economic and environmental context. Nowhere is the need for a “Just energy transition” starker than in the LDCs but the Report shows that despite this harsh reality, international support for LDC adaptation and sustainable development has fallen remarkably short of what is needed, both in terms of climate finance and of access to clean technologies. The Reports calls on the international community to be mindful of the institutional and capacity constraints that create scope for maladaptation in LDCs and to enhance targeted assistance to LDCs in line with their need for special and differential treatment.